Acetylation of cyclin A: a new cell cycle regulatory mechanism. (19th January 2010) - Mateo, Francesca; Vidal-Laliena, Miriam; Pujol, Maria Jesus; Bachs, Oriol
Abstract : Cyclin A must be degraded at prometaphase in order to allow mitosis progression. Nevertheless, the signals that trigger cyclin A degradation at mitosis have been largely elusive. In the present paper, we review the status of cyclin A degradation in the light of recent evidence indicating that acetylation plays a role in cyclin A stability. The emerging model proposes that the acetyltransferase PCAF [p300/CREB (cAMP-response-element-binding protein)-binding protein-associated factor] [perhaps also its homologue GCN5 (general control non-derepressible 5)] acetylates cyclin A at Lys 54, Lys 68, Lys 95 and Lys 112 during mitosis, leading to its ubiquitylation by the anaphase-promoting factor/cyclosome and its subsequent degradation via proteasome. Interestingly, these four lysine residues in cyclin A also participate in the regulation of cyclin A–Cdk (cyclin-dependent kinase) activity by modulating its interaction with Cdks.